Keuntungan Relatif dalam Inovasi Pelayanan Pengaduan Kerusakan Jalan Melalui Aplikasi M-Bonk - Ilmi Usrotin Choiriyah; Mokhamad Yusuf Chabibi (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study is to describe the innovation of road damage complaint services through the M-bonk application at the Dinas PU Bina Marga dan Pengairan, Sidoarjo Regency. The method used in this research is qualitative research. Qualitative research was chosen in the research on public service innovation in reporting road damage through the M-Bonk application so that the data obtained is more accurate with data acquisition through in-depth interviews, observation, and document utilization. In the Relative Advan- tage attribute, it is known that the presence of the M-Bonk application is to provide a real advantage, namely in the form of the speed of the new application which cuts a lot of time and doors that must be passed each report. Because the management of information or reports that come from the same door, namely through the M-Bonk application, and sheltered by one agency, namely the Dinas PU Bina Marga dan Pengairan. So that each report not only gets a fast response but also a fast response as well